2014
DOI: 10.1123/jmld.2013-0008
|View full text |Cite
|
Sign up to set email alerts
|

Self-Controlled Practice Within a Fixed Time Period Facilitates the Learning of a Basketball Set Shot

Abstract: Allowing self-control over various modes of instructional support has been shown to facilitate motor learning. Most research has examined factors that directly altered task-relevant information on a trial-to-trial basis (e.g., feedback). Recent research suggests that self-control (SC) effects extend to the manipulation of other types of factors (e.g., total number of practice trials completed). This research also illustrated that learners sometimes select a very small amount of practice when given latitude to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…Few studies have examined self-control of conditions that either have little or no apparent relationship to the task at hand. Exceptions in this regard include several studies by Post and colleagues (Post et al, 2011;Post, Fairbrother, Barros, & Kulpa, 2014) in which self-controlled opportunities for the number of practice attempts varied considerably between participants but resulted in better transfer or retention test performance for learner-controlled than yoked conditions. The number of practice trials is typically accorded a preeminent role among factors determining the extent of motor learning (e.g., Schmidt & Lee, 2011), yet fewer trials, if selfchosen, resulted in more effective learning than more trials imposed upon learners (Post et al, 2011(Post et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined self-control of conditions that either have little or no apparent relationship to the task at hand. Exceptions in this regard include several studies by Post and colleagues (Post et al, 2011;Post, Fairbrother, Barros, & Kulpa, 2014) in which self-controlled opportunities for the number of practice attempts varied considerably between participants but resulted in better transfer or retention test performance for learner-controlled than yoked conditions. The number of practice trials is typically accorded a preeminent role among factors determining the extent of motor learning (e.g., Schmidt & Lee, 2011), yet fewer trials, if selfchosen, resulted in more effective learning than more trials imposed upon learners (Post et al, 2011(Post et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Allowing learners to choose the extent of practice or the spacing of practice trials has been found to lead to more effective learning than yoked control conditions (Post, Fairbrother, & Barros, 2011;Post, Fairbrother, Barros, & Kulpa, 2014). Letting participants choose the order in which they wanted to perform balance exercises resulted in more effective learning of those exercises than not giving them this choice (Wulf & Adams, 2014).…”
Section: Incidental Choicesmentioning
confidence: 99%
“…Only eight studies were appraised as having a low risk of detection bias with regard to blinding of outcome assessors. 4653 All other studies did not provide sufficient information on outcome assessment but partially mitigated a possible distortion by measuring parameters that are rather obvious and therefore only provide a narrow margin of discretion. Potential attrition bias resulting from incomplete follow-up can largely be neglected.…”
Section: Resultsmentioning
confidence: 99%